The Influence of Leadership Style, Work Creativity, and Work Achievement on Human Resources Career Advancement: A Case Study in the Shipping Company of Serang Regency - Tata Rustandi*; Udin Suadma; Zulhan Zulhan (Riwayat: Educational Journal of History and Humanities, 2023)
The reason for this research is to distinguish and describe the impact of authority style and work imagination on work performance and its impact on the success of HR professionals in transportation organizations in the Serang Region. This study uses an information gathering strategy with a quantitative methodology. The estimation scale used in the survey in this study is the span scale, which is an information estimator that produces information that has a range of values that have significant meaning, even though the direct value is less important. The range scale used is concurclash. From these results, the Initiative Style in Job Execution is 〖T〗_statistik = 6.838 ≥ 1.96 with a P-Worth of 0.000 ≤ 0.05, it is argued that there is a critical positive effect between Administrative Style on Job Execution. Work Innovative on Job Execution T_statistic = 6.605 ≥ 1.96 with a P-Worth of 0.000 ≤ 0.05 concluded that there is a very large positive influence between Work Inventiveness on Job Execution. Initiative Style on HR Vocational Development T_statistik = 5.025 ≥ 1.96 with P-Worth 0.000 ≤ 0.05 concluded that there is a critical influence between Style of Authority on HR Professional Progress. Work Innovation on HR Vocational Development of 〖T〗_statistics = 3.903 ≥ 1.96 with a P-Worth of 0.001 ≤ 0.05 reasons that there is a very important influence between Work Imagination on HR Vocational Development. HR Vocational Improvement Work Implementation 〖T〗_statistics = 4.959 ≥ 1.96 with P-Worth 0.000 ≤ 0.05 concluded that there is a very large constructive influence between Work Execution on HR Professional Development.